Balls mill work index determination guide (Research, Society and Development, 2023)
The comminution stage is one of the main sources of energy consumption in the mineral processing plant and its objective is to reduce the ore to a sufficient size to enable the subsequent beneficiation processes. The operational costs of this step can be measured in laboratory by scientific formulas using a sample. The work index (WI) is a method used to forecast the energy consumption in the ore comminution and make it possible to scale up. This work aims to present the methodology for determining the work index by the ball-mill test through Bond's theory in view of the dissemination of this analysis methodology for industrial processes. This study has a theoretical stage with a bibliographic review on the method of applying the BWI determination by Bond's theory and a practical stage with the execution of the ball-mill test in the Mineral Processing Laboratory at Federal University of Ouro Preto (UFOP), using VKA WI software.